2005
DOI: 10.1111/j.1944-8287.2005.tb00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the Impact of Public Investment Neutral Across the Regional Income Distribution? Evidence from Mexico

Abstract: This paper investigates the contribution of public investment to the reduction of regional inequalities, with a specific application to Mexico. We use quantile regressions to examine the impact of public investment on regional disparities according to the position of each region in the conditional distribution of regional income. Results confirm the hypothesis that regional inequalities can indeed be attributed to the regional distribution of public investment, where the observed pattern shows that public inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Based on location theory and supply-demand theory, considering the complicated land market in China and the available databases, representative elements were chosen to analyze the spatially varying effects on residential land price after a series of statistical analyses, including immigrant population [22,[32][33][34], gross domestic product (GDP) [17,35] and investment in residential buildings [36][37][38][39][40]. The economic data are from the China City Statistical Yearbook directly [41].…”
Section: Impact Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on location theory and supply-demand theory, considering the complicated land market in China and the available databases, representative elements were chosen to analyze the spatially varying effects on residential land price after a series of statistical analyses, including immigrant population [22,[32][33][34], gross domestic product (GDP) [17,35] and investment in residential buildings [36][37][38][39][40]. The economic data are from the China City Statistical Yearbook directly [41].…”
Section: Impact Factorsmentioning
confidence: 99%
“…Thus the impact of GDP on China's land market cannot be neglected. Moreover, regional inequalities may be attributed to the regional unequal distribution of public investment [36]. As a part of real estate investment, construction cost is a main dynamic factor impacting land price.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the central s regional disparities. Using Mexican panel data and a quantile regression method, for example, Costa-i-Font and Rodriguez-Oreggia (2005) found that public investment smoothed over regional inequalities especially within the relatively richer regions. Fan and Zhang (2002), using rural data, found that infrastructure investments in the western rural areas are important in minimizing regional disparities.…”
Section: Introductionmentioning
confidence: 99%
“…The outreach of the ring line would thus narrow the income gap. Costa‐Font and Rodríguez‐Oreggia () investigates the contribution of public investment to the reduction of regional inequalities, the results show that public investment mainly helped to reduce regional inequalities among the richest regions.…”
Section: Introductionmentioning
confidence: 99%